2013
DOI: 10.1146/annurev-neuro-062111-150439
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Contributions to Visual Selective Attention

Abstract: The faculty of attention endows us with the capacity to process important sensory information selectively while disregarding information that is potentially distracting. Much of our understanding of the neural circuitry underlying this fundamental cognitive function comes from neurophysiological studies within the visual modality. Past evidence suggests that a principal function of the prefrontal cortex (PFC) is selective attention and that this function involves the modulation of sensory signals within poster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
200
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(222 citation statements)
references
References 77 publications
21
200
0
1
Order By: Relevance
“…This crossover interaction between task-complexity and brain modularity can be interpreted with respect to how tasks make use of a combination of domainspecific and domain-general processes. Previous task-related functional imaging studies have found that not only domain-specific regions, such as those for speech or visuo-spatial attention (Martin, 2003;Noudoost, Chang, Steinmetz, & Moore, 2010;Price, 2010;2012;Squire, Noudoost, Schafer, & Moore, 2013), but also domain-general attentional or cognitive control regions are activated during the performance of complex tasks involving, for instance, language comprehension or working memory (Fedorenko, Duncan, & Kanwisher, 2012;Nee et al, 2013). Moreover, the same patterns of synchronization of those regions have been reported even when there is no specific task (i.e., resting-state fMRI) (Fox & Raichle, 2007;Fox, Corbetta, Snyder, Vincent, & Raichle, 2006;Xiang, Fonteijn, Norris, & Hagoort, 2010).…”
Section: Modularity Of Brain Network and Behavioral Performancementioning
confidence: 99%
“…This crossover interaction between task-complexity and brain modularity can be interpreted with respect to how tasks make use of a combination of domainspecific and domain-general processes. Previous task-related functional imaging studies have found that not only domain-specific regions, such as those for speech or visuo-spatial attention (Martin, 2003;Noudoost, Chang, Steinmetz, & Moore, 2010;Price, 2010;2012;Squire, Noudoost, Schafer, & Moore, 2013), but also domain-general attentional or cognitive control regions are activated during the performance of complex tasks involving, for instance, language comprehension or working memory (Fedorenko, Duncan, & Kanwisher, 2012;Nee et al, 2013). Moreover, the same patterns of synchronization of those regions have been reported even when there is no specific task (i.e., resting-state fMRI) (Fox & Raichle, 2007;Fox, Corbetta, Snyder, Vincent, & Raichle, 2006;Xiang, Fonteijn, Norris, & Hagoort, 2010).…”
Section: Modularity Of Brain Network and Behavioral Performancementioning
confidence: 99%
“…Previous studies have found that the attention system is related to a variety of cortical areas, including the occipital cortex, PPC, FEF, aI/VLPFC, dACC and DLPFC; and, subcortically: the thalamus and the SC Eckstein, 2011;Saalmann and Kastner, 2011;Kim et al, 2012;Petersen and Posner, 2012;Zénon and Krauzlis, 2012;Krauzlis et al, 2013;Squire et al, 2013;Purcell et al, 2013;Peleen and Kastner, 2014;Cieslik et al, 2015;Katsuki and Constantinidis, 2015;Wimmer et al, 2015). Our fMRI data analysis results confirmed our hypothesis.…”
Section: Discussionsupporting
confidence: 89%
“…Microstimulation studies within the FEF have demonstrated that visual cortex activity is modulated by FEF neuronal activity; in turn, this modulation can lead to increased activity in visual areas, which varies according to the presence or absence of distractors and is related to the location of the target and the end point of saccades (Moore and Fallah, 2001;Moore and Amstrong, 2003;Moore and Fallah, 2004;Armstrong, Fitzgerald and Moore, 2006;Ekstrom, Roelfsema, Arsenault, Kolster and Vanduffel, 2009). Therefore, the FEF is seen as the interface between the saccadic system, the visual system, and the executive control system, not only because of the neural composition of the area, but also because a connection between saccadic movements and modulation of attention occurs within the FEF Fallah, 2001, 2004;Noudoost, Chang, Steinmetz and Moore, 2010;Squire, Noudoost, Schafer and Moore, 2013;Katsuki and Constantinidis, 2014).…”
Section: Frontal Cortexmentioning
confidence: 99%
“…In monkey visual cortex, spatial cues change the statistics of neuronal activity, and these changes are thought to reflect an increase in signal-to-noise synonymous with the spatially restricted changes in perceptual sensitivity characteristic of selective attention (2)(3)(4). The frontal and parietal cortex are also strongly implicated in the control of spatial attention (2,3).…”
mentioning
confidence: 99%
“…In monkey visual cortex, spatial cues change the statistics of neuronal activity, and these changes are thought to reflect an increase in signal-to-noise synonymous with the spatially restricted changes in perceptual sensitivity characteristic of selective attention (2)(3)(4). The frontal and parietal cortex are also strongly implicated in the control of spatial attention (2,3). Electrical microstimulation of neurons in frontal cortex of monkeys leads to shifts in selective attention mimicking the effects of visual cues (5); conversely, suppression of neural activity in frontal or parietal cortex leads to deficits in performance on attention-demanding tasks (6)(7)(8).…”
mentioning
confidence: 99%